Psychological burnout and its relationship to emotional balance among a sample of psychologists working with battered women - Mshharawi, Abeer Jibreel; Al-Mahdi, Somaya Khalifa Muhammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the relationship of psychological burnout with emotional balance among a sample of psychologists working with abused women. Among the psychologists working with abused women during the Corona pandemic, it reached (78.7%), which is a high level, that the level of emotional balance among psychologists working with abused women during the Corona pandemic reached (81.4%), which is a high level, that the Pearson correlation coefficient between psychological burnout And emotional balance equals (-0.865), which is a negative correlation coefficient, which means that the relationship is inverse, and there are no statistically significant differences in the level of burnout and emotional balance due to the study variables (age - academic degree - years of service), and the researcher recommends the need to pay attention to providing many courses Targeted training that provides psychiatrists with the most appropriate ways and methods to confront burnout, and work to provide job security for psychiatrists. For women working with abused women, work to implement counseling programs to reduce burnout, and develop emotional balance.